2021
DOI: 10.3390/met11060904
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Assisted Cracking in GMA Welding of High-Strength Structural Steel—A New Look into This Issue at Narrow Groove

Abstract: Modern arc processes, such as the modified spray arc (Mod. SA), have been developed for gas metal arc welding of high-strength structural steels with which even narrow weld seams can be welded. High-strength joints are subjected to increasingly stringent requirements in terms of welding processing and the resulting component performance. In the present work, this challenge is to be met by clarifying the influences on hydrogen-assisted cracking (HAC) in a high-strength structural steel S960QL. Adapted samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In the case of the composite tested, this condition was met for the preheating temperature of 300 • C. To obtain a crack-free surfaced coating, it was necessary to select the preheating temperature and control the inter-pass temperature. Preheating the material before surfacing reduces shrinkage stress [39] and the hardness in the heat-affected zone [40], while also reducing the risk of hydrogen cracks [41]. In the analyzed case, the factors that influenced the necessity to use preheating were the high carbon equivalent value, CEV = 0.66% and the high-power density of the heat source, which translated into low linear welding energy.…”
Section: Non-destructive Testing Resultsmentioning
confidence: 97%
“…In the case of the composite tested, this condition was met for the preheating temperature of 300 • C. To obtain a crack-free surfaced coating, it was necessary to select the preheating temperature and control the inter-pass temperature. Preheating the material before surfacing reduces shrinkage stress [39] and the hardness in the heat-affected zone [40], while also reducing the risk of hydrogen cracks [41]. In the analyzed case, the factors that influenced the necessity to use preheating were the high carbon equivalent value, CEV = 0.66% and the high-power density of the heat source, which translated into low linear welding energy.…”
Section: Non-destructive Testing Resultsmentioning
confidence: 97%
“…This area of cracking is typical for underwater processes [16,18]. Furthermore, Schaupp et al [35] in their next paper showed that S960 UGSS is characterized by a high risk for hydrogen-assisted cracking both in the weld metal and in the HAZ. These investigations suggest that the S960 steel may be characterized by very high susceptibility to cold cracking in underwater conditions, due to a high amount of water during joining in this environment.…”
Section: Introductionmentioning
confidence: 83%
“…More and more attention has been paid to the safety of transportation equipment [1][2][3]. Facing the energy crisis, hydrogen-fueled vehicles are recognized as a most promising solution [4][5][6][7]. Compared with electric vehicles, when refueling with energy, the hydrogen vehicle has advantages of technical simplicity and high filling rates [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that hydrogen embrittlement (HE) has become a serious problem since high-strength steel became widely used [5,7,13,14]. With the widespread application of aluminum alloys, it's found that aluminum and its alloys also have a higher hydrogen content [15][16][17].…”
Section: Introductionmentioning
confidence: 99%